Determination of gyro frequency from critical frequency measurements over Parit Raja, Malaysia - Zain A.F.Mohd.; Bin Abdullah S.; Rhazali Z.A. (2023)
The critical frequencies of the ionosphere are observed from ionograms to determine the gyro frequencies. The ionograms are obtained from the Parit Raja station using an ionosonde at latitude 152' N and longitude 10348' E which is close to the geomagnetic equator at geographic latitude 5N. Preliminary results show that the gyro frequencies obtained are between 0.2 MHz and 1.4 MHz. 2013 IEEE.